Reliability of horizontal force–velocity–power profiling during short sprint-running accelerations using radar technology. Issue 1 (2nd January 2019) - Simperingham, Kim David; Cronin, John B.; Pearson, Simon N.; Ross, Angus
Abstract: Radar technology can be used to perform horizontal force–velocity–power profiling during sprint-running. The aim of this study was to determine the reliability of radar-derived profiling results from short sprint accelerations. Twenty-seven participants completed three 30 m sprints (intra-day analysis), and nine participants completed the testing session on four separate days (inter-day analysis). The majority of radar-derived kinematic and kinetic descriptors of short sprint performance had acceptable intra-day and inter-day reliability [intraclass correlation coefficient (ICC) ≥ 0.75 and coefficient of variation (CV) ≤ 10%], but split times over the initial 10 m and some variables that include a horizontal force component had only moderate relative reliability (ICC = 0.49–0.74). Comparing the average of two sprint trials between days resulted in acceptable reliability for all variables except the relative slope of the force–velocity relationship ( S Fvrel ; ICC = 0.74). Practitioners should average sprint test results over at least two trials to reduce measurement variability, particularly for outcome variables with a horizontal force component and for sprint distances of less than 10 m from the start.